Analysis of the characteristics of paulownia lignocellulose and hydrogen production potential via photo fermentation. (January 2022) - Zhang, Quanguo; Jin, Peng; Li, Yameng; Zhang, Zhiping; Zhang, Huan; Ru, Guangming; Jiang, Danping; Jing, Yanyan; Zhang, Xueting
Graphical abstract: Highlights: The composition of different Paulownia biomass was analyzed. The biohydrogen production potential of paulownia biomass was evaluated. The leaves of Paulownia showed the maximum hydrogen yield and energy conversion. Paulownia jianshiensis leaves have the highest CHY of 98.83 mL/g TS and ECE of 7.18%. Abstract: Paulownia biomass is rich in carbohydrates, making which a potential feedstock for biohydrogen production. In the study, different parts and varieties of Paulownia were chose as substrates to evaluate hydrogen production potential of paulownia lignocellulose via biohydrogen production by photo fermentation (BHPPF) and energy conversion efficiency (ECE). Results showed the highest cumulative hydrogen yield (CHY) of 67.11 mL/g total solids (TS) and ECE of 4.74% were obtained from leaves of Paulownia, which were 121.06% and 115.45% higher than those of the branches. Moreover, Paulownia jianshiensis leaves were found to be the best variety for BHPPF, with the maximum CHY of 98.83 mL/g TS and ECE of 7.18%. Using Paulownia waste as the substrate to produce hydrogen helps broaden the range of raw materials for BHPPF and improve the economic utilization of forestry waste.